2017
DOI: 10.1007/s00127-017-1437-2
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of socioeconomic position and distance on mental health care utilization: a nationwide Danish follow-up study

Abstract: PurposeTo determine the impact of socioeconomic position (SEP) and distance to provider on outpatient mental health care utilization among incident users of antidepressants.MethodA nationwide register-based cohort study of 50,374 person-years.ResultsPersons in low SEP were more likely to have outpatient psychiatrist contacts [odds ratio (OR) 1.25; confidence interval (CI) 1.17–1.34], but less likely to consult a co-payed psychologist (OR 0.49; CI 0.46–0.53) and to get mental health service from a GP (MHS-GP) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 31 publications
2
41
1
2
Order By: Relevance
“…The WHO-AIMS study in Nepal had found that 54% of inpatients were male. 2 Similar findings have been noted by other studies, 7,16,17 [22][23][24][25][26][27] Zulian et al reported the caseload decreased with increasing distance and found a 60% decrease in inpatient wards at a distance of 10km. 26 Majority of patients(88.4%) were Hindu by religion followed by Kirat(5.4%).…”
Section: Discussionsupporting
confidence: 78%
“…The WHO-AIMS study in Nepal had found that 54% of inpatients were male. 2 Similar findings have been noted by other studies, 7,16,17 [22][23][24][25][26][27] Zulian et al reported the caseload decreased with increasing distance and found a 60% decrease in inpatient wards at a distance of 10km. 26 Majority of patients(88.4%) were Hindu by religion followed by Kirat(5.4%).…”
Section: Discussionsupporting
confidence: 78%
“…Several studies have shown that increase in distance decreases the likelihood of service utilization in mental health. [8][9][10][12][13][14] Similarly, there was significant association of proximity to hospital with LoS, those from same and nearby districts had shorter LoS as compared to others. In our clinical experience, those from nearby places, who could follow up regularly to OPD are discharged earlier as compared to those from faraway places who could have difficulty in following up regularly.…”
Section: Discussionmentioning
confidence: 93%
“…This was done as literature have shown the role of proximity to the service in mental health service utilization. [8][9][10] The data were entered into MS Excel and analysed using the SPSS version 20.0. For descriptive statistics, percentage, mean, range and standard deviation were calculated.We used bivariate and multiple logistic regression analysis to find the strength of association of LoS with variables of interest and adjusted Odds Ratio (aOR) were calculated with 95% confidence interval (CI).…”
Section: Methodsmentioning
confidence: 99%
“…G is the Gini coeffi cient, y t is the percentage of the total number of years of education in the I population that has served in the region. The n in this article is divided into 5 levels (Packness, et al, 2017;Mok, 2015). Among them, one refers to illiteracy, the number of years of education 0.…”
Section: Figure 1 the Division Of Gini Coeffi Cient Section Of Worldmentioning
confidence: 99%